Synthesis of Hierarchical Porous SAPO-34 and Its Catalytic Activity for 4,6-Dimethyldibenzothiophene - Wang, Hua-Qin; Cui, Yun-Qi; Ding, Ya-Long; Xiang, Mei; Yu, Pei; Li, Rong-Qiang (Frontiers in Chemistry, 2022)
Zeolite SAPO-34 has been widely used in industrial because of its special pore structure and wide distribution of acid sites in the pore channel. However, traditional SAPO-34 with small pore size suffers for carbon deposition and deactivation in catalytic reactions, and its powerlessness for catalytic conversion of bulky organic molecules limits the industrial application of SAPO-34. Meanwhile, impurities of SAPO-5 which has weak acidity leading to rapid catalyst deactivation is easy to appear in SAPO-34 zeolite. Therefore, it is of great significance to synthesize SAPO-34 zeolite containing mesoporous pore structure, which can significantly improve the transfer of molecules in zeolites. In this paper, SAPO-34 zeolite with hierarchical pore structure was synthesized, and its hydrodesulfurization performance for 4,6-dimethyldibenzothiophene (4,6-DMDBT) was studied in a fixed bed reactor. The characteristic results show that BET specific surface area, micropore volume and mesoporous volume of synthesized SAPO-34 is 754 m2·g-1, 0.25 and 0.23 cm3·g-1 respectively, and the pore size is mainly concentrated at 4 nm. The catalytic conversion of 4,6-DMDMT with Co and Mo supported SAPO-34 is about 83 %, which is much higher than catalytic performance of Al2O3.